Photoelectrochemical and photocatalytic activities of improved TiO2 nanotubes using Ag+ ion implantation and RGO deposition. (2nd January 2022) - Liao, Bin; Chen, Lin; Luo, Jun; Pang, Pan; Wang, Guoliang
ABSTRACT: Highly efficient RGO-Ag-TNTs ternary photocatalytic composites were synthesized. In this work, Ag+ ions were implanted into Ti foils to form Ag-doped TNTs, and then GO was reduced to RGO on the surface of Ag-doped TNTs. The properties of Ag-TNTs and RGO-Ag-TNTs were determined using XRD, FESEM, XPS and UV-Vis DRS. The photoelectrochemical performance of those composites was confirmed using current density, transient photocurrent and electrochemical impedance spectroscopy. The photocatalytic activities of the samples were also assessed using the decomposition of methyl orange. The Ag-TNTs sample with an implanted dose of 5 × 10 16 ions/cm 2 exhibited the best photoelectrochemical and photocatalytic performance. The photoelectrochemical and photocatalytic capabilities of Ag-TNTs were improved further by the deposition of RGO. The outstanding properties of RGO-Ag-TNTs composites are ascribed to the synergism of modulated band structure of Ag-TNTs and the excellent electronic conductivity of the deposited RGO sheets. GRAPHICAL ABSTRACT: UF0001